2021
DOI: 10.1007/s00220-021-04146-3
|View full text |Cite
|
Sign up to set email alerts
|

Remarks on Stationary and Uniformly-rotating Vortex Sheets: Rigidity Results

Abstract: In this paper, we show that the only solution of the vortex sheet equation, either stationary or uniformly rotating with negative angular velocity $$\Omega $$ Ω , such that it has positive vorticity and is concentrated in a finite disjoint union of smooth curves with finite length is the trivial one: constant vorticity amplitude supported on a union of nested, concentric circles. The proof follows a desingularization argument and a calculus of variations flavor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 42 publications
0
23
0
Order By: Relevance
“…We refer to [13,14,40,43] for single rotating patches, [26,27] for doubly connected V-states, [42,39] for corotating and counter-rotating vortex pairs and [33] for steady states. See [34] for further properties of rotating solutions and [35,36] for the case of the vortex-sheet problem. See [29,41,58] for related constructions.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…We refer to [13,14,40,43] for single rotating patches, [26,27] for doubly connected V-states, [42,39] for corotating and counter-rotating vortex pairs and [33] for steady states. See [34] for further properties of rotating solutions and [35,36] for the case of the vortex-sheet problem. See [29,41,58] for related constructions.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…In the case of 2D Navier-Stokes, Koch-Nadirashvili-Seregin-Šverák also proved a Liouville theorem in [66]. See also [49,50] where together with Yao we proved rigidity and flexibility results for the vortex sheet problem.…”
Section: D Euler Rigidity and Construction Of Stationary Solutionsmentioning
confidence: 71%
“…This remarkable result indicates that solutions bifurcated from concentric circles can be constructed in the same way, and constitute the second class of vortex sheet solutions. In their follow-up work [14], they have further showed that one can not expect vortex sheets other than concentric circles when ω ≥ 0 and Ω ≤ 0.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…and angular velocity Ω. (Ω > 0 for counterclockwise) Recently, Gómez-Serrano et al [13] gave another vortex sheet supported on a closed curve. By Lyapunov-Schmidlt reduction and degenerate bifurcation, they obtained two curves of solution bifurcated from one trivial solution, which is a unit circle at specific angular velocity.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%